Lay Bystanders' Perspectives on What Facilitates Cardiopulmonary Resuscitation and Use of Automated External Defibrillators in Real Cardiac Arrests. Issue 3 (March 2017) - Malta Hansen, Carolina; Rosenkranz, Simone Mørk; Folke, Fredrik; Zinckernagel, Line; Tjørnhøj‐Thomsen, Tine; Torp‐Pedersen, Christian; Sondergaard, Kathrine B.; Nichol, Graham; Hulvej Rod, Morten
Abstract : Background: Many patients who suffer an out‐of‐hospital cardiac arrest will fail to receive bystander intervention (cardiopulmonary resuscitation [CPR] or defibrillation) despite widespread CPR training and the dissemination of automated external defibrillators (AEDs). We sought to investigate what factors encourage lay bystanders to initiate CPR and AED use in a cohort of bystanders previously trained in CPR techniques who were present at an out‐of‐hospital cardiac arrest. Methods and Results: One‐hundred and twenty‐eight semistructured qualitative interviews with CPR‐trained lay bystanders to consecutive out‐of‐hospital cardiac arrest, where an AED was present were conducted (from January 2012 to April 2015, in Denmark). Purposive maximum variation sampling was used to establish the breadth of the bystander perspective. Twenty‐six of the 128 interviews were chosen for further in‐depth analyses, until data saturation. We used cross‐sectional indexing (using software), and inductive in‐depth thematic analyses, to identify those factors that facilitated CPR and AED use. In addition to prior hands‐on CPR training, the following were described as facilitators: prior knowledge that intervention is crucial in improving survival, cannot cause substantial harm, and that the AED will provide guidance through CPR; prior hands‐on training in AED use; during CPR performance, teamwork (ie, support), using the AED voice prompt and a ventilation mask, as well as demonstrating leadership and feeling a moral obligation to act. Conclusions: Several factors other than previous hands‐on CPR training facilitate lay bystander instigation of CPR and AED use. The recognition and modification of these factors may increase lay bystander CPR rates and patient survival following an out‐of‐hospital cardiac arrest.